The Demand for Illegal Migration and Market Outcomes - Horst Entorf; Jochen Möbert (Technische Universität Darmstadt, Department of Law and Economics, 2004)
This article summarizes important aspects of illegal immigration. We analyse incentives of illegal immigrants as well as those of their employers by applying basic principles of labour economics, and by customising the workhorse of the economic theory of crime to suit the labour market for illegals immigrants. In addition, we describe the economic and social consequences of possible market outcomes.
Keywords: F22; J31; 330